2022
DOI: 10.1155/2022/5160705
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis Reveals PTK6 as a Prognostic Biomarker Involved in the Immunosuppressive Microenvironment in Breast Cancer

Abstract: The significant mortality rate that is currently experienced by female breast cancer (BC) patients highlights the importance of locating potent and dependable biomarkers in BC patients. Over the past few years, a number of studies have demonstrated that PTK6 was dysregulated in a variety of cancers. However, its expression and the clinical importance it may have in patients with BC have not been explored. Based on datasets from the TCGA database and GTEx database, we studied the expressions and functions of PT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
(43 reference statements)
1
3
0
Order By: Relevance
“…Additionally, the KEGG pathway analysis indicated that PTK6 could play an essential role in human tumor formation, as with the previous study [ 73 ], especially in renal cell carcinoma. The PPI network and KEGG pathway analysis suggested that PTK6 was connected to the HIF1α pathway ( Fig.…”
Section: Discussionsupporting
confidence: 81%
“…Additionally, the KEGG pathway analysis indicated that PTK6 could play an essential role in human tumor formation, as with the previous study [ 73 ], especially in renal cell carcinoma. The PPI network and KEGG pathway analysis suggested that PTK6 was connected to the HIF1α pathway ( Fig.…”
Section: Discussionsupporting
confidence: 81%
“…These results suggest that inhibition of PTK6 may be a potential target for TNBC therapy. Wang et al also found that PTK6 was associated with poor prognosis of breast cancer [ 28 ]. PTK6 expression was not associated with DFS in the LNM- group.…”
Section: Resultsmentioning
confidence: 99%
“…PTK6, a non-receptor tyrosine kinase, has been shown to promote metastasis and progression of breast cancer when its expression is increased [21]. Additionally, patients who had high levels of PTK6 expression had a shorter overall survival and disease-speci c survival, as well as PTK6 expression was shown to correlate with the prognosis of breast cancer patients with different clinical statuses [22].…”
Section: Discussionmentioning
confidence: 99%